Determinants of Economic Growth in South Buru District - Sabar Wael; Dientje Rumerang; Yerimias Manuhutu (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Economic growth is a complex phenomenon influenced not only by conventional economic factors, such as investment and labor availability, but also by non-economic determinants, including education levels, health conditions, and other social variables. This study aims to analyze the effects of labor, regional government expenditure, and electricity production on economic growth in South Buru Regency. An explanatory quantitative research method was employed in this study. Data were collected through a literature review of relevant secondary sources. The data were analyzed using multiple linear regression analysis. The results indicate that labor has a positive and statistically significant effect on economic growth. Regional government expenditure also has a positive and statistically significant effect on economic growth. Likewise, electricity production has a positive and statistically significant effect on economic growth. Simultaneously, labor, regional government expenditure, and electricity production are shown to be key factors influencing the dynamics of economic growth in South Buru Regency